Assessment of fresh and cryopreserved testicular tissues from (pre)pubertal boys during organ culture as a strategy for in vitro spermatogenesis. Issue 12 (20th December 2019) - Portela, J M D; de Winter-Korver, C M; van Daalen, S K M; Meißner, A; de Melker, A A; Repping, S; van Pelt, A M M
Abstract: STUDY QUESTION: Can the organ culture method be applied to both fresh and cryopreserved human (pre)pubertal testicular tissue as a strategy for in vitro spermatogenesis? SUMMARY ANSWER: Although induction of spermatogenesis was not achieved in vitro, testicular architecture, endocrine function and spermatogonial proliferation were maintained in both fresh and cryopreserved testicular tissues. WHAT IS KNOWN ALREADY: Cryopreservation of a testicular biopsy is increasingly offered as a fertility preservation strategy for prepubertal cancer patients. One of the proposed experimental approaches to restore fertility is the organ culture method, which, in the mouse model, successfully allows for in vitro development of spermatozoa from testicular biopsies. However, complete spermatogenesis from human prepubertal testicular tissue in such an organ culture system has not been demonstrated. STUDY DESIGN, SIZE, DURATION: Testicular tissue was collected from nine (pre)pubertal boys diagnosed with cancer (ranging from 6 to 14 years of age) admitted for fertility preservation before treatment. Testicular biopsies were either immediately processed for culture or first cryopreserved, using a controlled slow freezing protocol, and thawed before culture. Organ culture of testicular fragments was performed in two different media for a maximum period of 5 weeks, targeting early cellular events (viability, meiosis and somatic differentiation) in vitro . PARTICIPANTS/MATERIALS, SETTING, METHODS: Fresh and cryopreserved-thawed testis fragments (1–2 mm 3 ) were cultured at a gas–liquid interphase (34°C, 5% CO2 ) in Minimum Essential Medium alpha + 10% knock-out serum replacement medium containing 10 −7  M melatonin and 10 −6  M retinoic acid, with or without 3 IU/L FSH/LH supplementation. The effect of culture conditions on testicular fragments was weekly assessed by histological evaluation of germ cell development and immunohistochemical identification of spermatogonia (using MAGEA4), proliferative status of spermatogonia and Sertoli cells (using proliferating cell nuclear antigen [PCNA]), intratubular cell apoptosis (by terminal deoxynucleotidyl transferase-mediated dUTP nick-end labelling) and Sertoli cells maturation (using Anti-Müllerian Hormone [AMH] versus Androgen Receptor [AR]). Additionally, Leydig cells' functionality was determined by measuring testosterone concentration in the culture media supernatants. MAIN RESULTS AND THE ROLE OF CHANCE: Neither fresh nor cryopreserved human (pre)pubertal testicular fragments were able to initiate spermatogenesis in our organ culture system. Nonetheless, our data suggest that fresh and cryopreserved testicular fragments have comparable functionality in the described organ culture conditions, as reflected by the absence of significant differences in any of the weekly evaluated functional parameters. Additionally, no significant differences were found between the two tested media when culturing fresh and cryopreserved human testicular fragments. Although spermatogonia survived and remained proliferative in all culture conditions, a significant reduction of the spermatogonial population ( P  ≤ 0.001) was observed over the culture period, justified by a combined reduction of proliferation activity ( P  ≤ 0.001) and increased intratubular cell apoptosis ( P  ≤ 0.001). We observed a transient increase in Sertoli cell proliferative activity, loss of AMH expression ( P  ≤ 0.001) but no induction of AR expression. Leydig cell endocrine function was successfully stimulated in vitro as indicated by increased testosterone production in all conditions throughout the entire culture period ( P  ≤ 0.02). LARGE SCALE DATA: N/A LIMITATIONS, REASONS FOR CAUTION: Although not noticeable in this study, we cannot exclude that if an optimized culture method ensuring complete spermatogenesis in human testicular fragments is established, differences in functional or spermatogenic efficiency between fresh and cryopreserved tissue might be found. WIDER IMPLICATIONS OF THE FINDINGS: The current inability to initiate spermatogenesis in vitro from cryopreserved human testicular fragments should be included in the counselling of patients who are offered testicular tissue cryopreservation to preserve fertility. STUDY FUNDING/COMPETING INTEREST(S): This project was funded by EU-FP7-PEOPLE-2013-ITN 603568 `Growsperm'. None of the authors have competing interests. TRIAL REGISTRATION NUMBER: Not applicable.